SUSTAINABLE ENVIRONMENT FOR SUSTAINABLE DEVELOPMENT - Karyanto, Puguh (Prodi Pendidikan Biologi FKIP UNS, 2011)
ABSTRAK Sustainable development is a famous concept and strategy to balance the state between human anthropogenic activity and environmental conservation. It is conceptualized mainly, to address the challenge of ensuring continual human civilization under the limitedly available natural resources. There is no dispute to value ecosystem services to be included into the idea of sustainable development. However, since sustainable development is defined as it is affected by many vested interests, the precise ecosystem and environmental aspects that are regarded as critical for sustainable development are also under debate. Essentially, the emerging debates deal with criticism towards giving value on particular environmental properties and, deal with the judgement of whether they are considered as critical or less critical for the sustainability of particular developmental activities. Hence, this paper is aimed to provide ideas to bridge the presence polemics by presenting the two important ideas in combination, sustainable environment and socio ecological sustainability as a considerable ideas to achieve sustainable development. To have the research?s goal the criteria of millennium ecosystem assessment and the socio ecological indicator proposed are is scrutinized. Indeed, human activity is considered as sustainable if it is put in position with socio ecological indicators. In addition to this, extending human?s moral standing to the environment will be importantly underpin the achievement of sustainable environment and therefore, the sustainable development. Kata kunci : Sustainable environment, Sustainable development